Water quality: unclogging the Khari river: stakeholders come together to halt pollution - Mudrakartha, Srinivas; Srinath, J.; Sheth, Jatin (2006)
This case study reports on how the variousstakeholders came together to alleviate the problem of effluents discharged by factories in the industrial estates on theeastern periphery of Ahmedabad into the Kharicut canal that flows into the Khari, a tributary of the Sabarmati. - Reproduced.
Keywords: Pollution; Water quality